Economic impact of localized cutaneous leishmaniasis on adult patients of a referral service in Belo Horizonte, Minas Gerais State, Brazil - Endi Lanza Galvão; Talia Santana Machado de Assis; Mariana Junqueira Pedras; Gláucia Fernandes Cota; Taynãna César Simões; Ana Rabello (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Cutaneous leishmaniasis (CL) is a disease associated with low-income populations. Thus, in assessing the burden of this disease, it is important to include its economic impact on individuals. We aimed to evaluate CL economic impact on patients treated at a referral service in the State of Minas Gerais, Brazil. This is a cross-sectional study based on the analysis of interviews and medical records from which we assembled direct medical and non-medical costs related to CL, from a societal perspective. One hundred patients were included; 50% had a monthly per capita income of up to USD 259.60 and spent on average USD 187.32 with the disease, representing an average monthly impact of 22.5% (USD 133.80). The disease imposed direct medical costs, such as: private medical appointments, medications, medical exams, dressing material, and co-participation in health insurances. Direct non-medical costs were mainly related to patients' transportation to health centers (USD 4,911.00), but also included medically-necessary care, food, and domestic and business outsourcing services. Although the Brazilian public health system guarantees access to health care, CL still represents a substantial economic impact for patients. The main action to reduce the expenses with this disease is decentralizing services for CL diagnosis and therapeutic approach, as well as increasing their efficiency.